Drug Delivery Systems for Respiratory Diseases: Insights into the Therapeutic Innovations for Pulmonary Administration - Mershen Govender; Yahya E. Choonara (Pharmaceutics)
Respiratory issues, such as asthma, chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, pulmonary hypertension, and respiratory infections, are amongst the most common and debilitating medical conditions experienced worldwide, affecting millions of patients annually [...]